Androcentrism and conservatism within climate obstructionism. The case of the think tank CLINTEL in The Netherlands - Moreno-Soldevila, Mayte (Ámbitos. Revista Internacional de Comunicación, 2022)
Within the climate countermovement, neoliberal think tanks have played a predominant role in both the United States and Europe. There are links between climate obstructionism and ideologies such as conservatism and the extreme right; androcentrism, patriarchal worldviews and industrial masculinities, and whiteness and xenosceptic ideologies. This research takes as a case study the Dutch think tank CLINTEL, which, despite having been founded in 2019, has managed to get a declaration against the climate emergency to members of the European Parliament, which has been signed by climate action contrarians from all over the world. This paper analyses the contrarian framings present in this declaration based on the typology established by Almiron et al. (2020). In addition, this research makes a gendered discursive analysis of the discussion about this statement in a forum of the European Parliament, where CLINTEL met with members of the far-right Dutch party Forum van Democratie (FvD), part of the European Conservatives and Reformists group. The study on CLINTEL's statement shows that the think tank uses similar frames as other European denialist think tanks. Its climate declaration has a significant gender bias, with an overwhelming over-representation of men among the signatories. This, together with the discursive analysis of its discussion with members of the European Parliament, is a contribution to the emerging line of research on industrial masculinities and climate change obstructionism. This paper provides information on the think tank CLINTEL, helping to fill a knowledge gap on the climate change countermovement in the Netherlands.